Antidiabetic effects and mechanisms of action of γ-conglutin from lupin seeds - Tapadia, Mrunmai; Johnson, Stuart; Utikar, Ranjeet; Newsholme, Philip; Carlessi, Rodrigo (ELSEVIER, 2021)
The glucose modulating properties of lupin have been attributed to its seed protein γ-conglutin. Here we explored the antidiabetic potential of γ-conglutin purified from lupin seeds in-vitro. To mimic the effects of an orally administered supplement, purified γ-conglutin was hydrolysed by gastrointestinal proteolytic enzymes and the resulting peptides evaluated for their antidiabetic effects in pancreatic β-cells and primary human skeletal muscle myotubes. γ-conglutin peptides did not promote insulin secretion in β-cells but elicited a potent insulin-mimetic action by activating insulin signalling pathways responsible for glycogen, protein synthesis, and glucose transport into myotubes. Additionally, the peptides potently suppressed the activity of DPP4 indicating their potential to increase the half-life of incretin hormones in circulation. These results substantiate the health benefits of consuming lupin seeds as part of a healthy diet and can drive the current market for lupins from primarily stockfeed, towards value-added lupin-based food products for human consumption.